Influence of the public spaces of Campus Capanique SL-02 in the university formation of the students of the FAU-UPT- 2017 - Almonte Durand, Catherine Alessandra (2018)
The objective of this study is to determine how the public spaces of Campus Capanique SL-02 influence the university education of students of the Faculty of Architecture and Urbanism of the Private University of Tacna, considering the Infrastructure factor as a predominant scope belonging to the institutional welfare indicator, promoting within this factor the importance of the degree of excellence in landscape quality that should exist in each physical space. The research is of the pure type, with an explanatory design. The study population was made up of students from the Faculty of Architecture and Urbanism. The sample size was 200 students randomly chosen. The instrument was the survey validated with the Cronbach's Alpha coefficient, and applied to the representative sample. The results were processed and analyzed with the statistical program SPSS. The results are expressed in summary tables where the levels of behavior presented by each variable are established. The results allow establishing that public spaces have significant influence on university education in the Faculty of Architecture and Urbanism. In conclusion, it can be established that the public spaces of Campus SL-02 of the Faculty of Architecture and Urbanism condition the quality of the training of the students of the Architecture career